Bridging social distance during social distancing: Exploring social talk and remote collegiality in video conferencing - Bleakley, Anna; Rough, Daniel; Edwards, Justin; Doyle, Philip; Dumbleton, Odile; Clark, Leigh; Rintel, Sean; Wade, Vincent; Cowan, Benjamin R. (Human–Computer Interaction, 2022)
Video conferencing systems have long facilitated work-related conversations among remote teams. However, social distancing due to the COVID-19 pandemic has forced colleagues to use video conferencing platforms to additionally fulfil social needs. Social talk, or informal talk, is an important workplace practice that is used to build and maintain bonds in everyday interactions among colleagues. Currently, there is a limited understanding of how video conferencing facilitates multiparty social interactions among colleagues. In our paper, we examine social talk practices during the COVID-19 pandemic among remote colleagues through semi-structured interviews. We uncovered three key themes in our interviews, discussing 1) the changing purposes and opportunities afforded by using video conferencing for social talk with colleagues,2) how the nature of existing relationships and status of colleagues influences social conversations and 3) the challenges and changing conversational norms around politeness and etiquette when using video conferencing to hold social conversations. We discuss these results in relation to the impact that video conferencing tools have on remote social talk between colleagues and outline design and best practice considerations for multiparty videoconferencing social talk in the workplace. KEYWORDS: Communication; video conferencing; collegiality; social talk; COVID; colleagues; working from home; multiparty